A CADASIL-Like Case with a Novel Noncysteine Mutation of the NOTCH3 Gene and Granular Deposits in the Renal Arterioles. (9th March 2015) - Nakamura, Kuniyuki; Ago, Tetsuro; Tsuchimoto, Akihiro; Noda, Nozomi; Nakamura, Asako; Ninomiya, Toshiharu; Uchiumi, Takeshi; Tsuruya, Kazuhiko; Kamouchi, Masahiro; Ooboshi, Hiroaki; Kitazono, Takanari
Abstract : We herein report the finding of a 62-year-old male, who developed dysarthria and dysphagia, with cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy- (CADASIL-) like cerebral lesions. He also suffered from slowly progressive renal failure with the findings of granular deposits similar to electron-dense granular osmiophilic material in the renal arterioles. We found a novel heterozygous missense mutation of the NOTCH3 gene, c.4039G>C in exon 24, resulting in a p.Gly1347Arg substitution in its extracellular domain. The noncysteine substitution may underlie the pathogenesis of white matter lesions in the brain and of the chronic renal failure in the present case.